NEW HORIZONS OF IDENTITY DISCOURSE AS A CHALLENGE TO THE REBRANDING OF THE UNIVERSALIST MACROETHICS - Komisar, Liudmyla (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
The introduction examines the modern phenomena of "diffusion" of personal and social identity and the stages of its formation in the palimpsests of the network society. The aim of the article is to explore new horizons of identity discourse both in a holistic transdisciplinary dimension and in the light of rebranding the universalist macroethics. Research methods. The problematics of the article involves the use of interdisciplinary methods: structuralist-phenomenological, logical-analytical, ethical-axiological, culturalphilosophical, hermeneutic-ontological and comparative, as well as the methods of "concept history", "pre-understanding", "commentary", "exegesis" and "interpretation". The results of the study distinguish the paradigmatic levels of identity, such as ethno- /macroethics, ethics of authenticity, responsive phenomenology and dialogue philosophy as the factors present in the formation of the concept of "Europeanness". The phenomenon of identity "erosion" is passed through the "matrix of ideologies", with an eye to the postmodern "carnival logic" in mass digital communication as one of the reasons for the paradox of the devaluation of ethical and rightwing universalism. The Ukrainian ethics of authenticity / monadity, which posits the ability of the modern subject to personal "selfdevelopment", appears as a demonstrative prism for the constitution of the discourse of identity. At this level, an individual, acquiring social and cultural self-identification, emerges as a person capable of adequately representing his/her era, time, nation. The discussion outlines modern polylogues among different dimensions of identity paradigms, with an emphasis on both the leading criteria for the formation of a common European identity and the openness of this issue. Considerable attention is paid to the leading criteria for the formation of personal self-identity and its influence on the formation of identities in the light of axiological, cultural and social backgrounds. The conclusions demonstrate that modern dimensions of both theoretical and practical researches on the ontology of identity require a transdisciplinary approach: socio-philosophical, ecological, political-ideological, ethical-axiological, etc. Therefore, the current discourse of identity – both at the personal level of consciousness (in self-awareness reflections) – and at the collective level of society (in permanent social communication) is at the stage of formation, creating an open polylogue for the emergence of new currents, paradigms and discussions.